2017
DOI: 10.1093/neuros/nyx392
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Volume Assessment in Low-Grade Gliomas: A Comparison of Preoperative Magnetic Resonance Imaging to Coregistered Intraoperative 3-Dimensional Ultrasound Recordings

Abstract: The tumor volumes of LGGs segmented from intraoperative US images were most often smaller than the tumor volumes segmented from preoperative MRIs. There was a much better match between the 2 modalities in astrocytomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The intra-rater tumor volume difference for the ground truth was reported in. 14 This same volume difference was then computed between the ground truth and the segmentations estimated with the 3D network. The two outliers were excluded because comparing non-overlaping volumes is meaningless.…”
Section: Results For the 3-d Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The intra-rater tumor volume difference for the ground truth was reported in. 14 This same volume difference was then computed between the ground truth and the segmentations estimated with the 3D network. The two outliers were excluded because comparing non-overlaping volumes is meaningless.…”
Section: Results For the 3-d Networkmentioning
confidence: 99%
“…For each patient, two pMR volumes (T1w and T2-FLAIR scans) and three iUS 3-D volumes were acquired before, during, and after resection. We used as the ground truth (GT) the manual segmentations by Munkvold et al, 14 which were available for 17 volumes before resection. Figure 1 shows examples of ground truth segmentations for three cases.…”
Section: Datamentioning
confidence: 99%
“…For the universal AVQ method proposed here, the first step is to convert DICOM data into a 3D model. Since 3D Slicer has been commonly used in various medical and bioengineering fields, we elected to use it as the reference method 1,11,12,20,31) . Although 3D Slicer has been previously used to define cerebral vascular anatomy and obtain vascular parameters, to our knowledge, it has not been used to measure aneurysm volume 4,[13][14][15]18,19) .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the newest and perhaps the most detailed data presented by leading Norwegian group showed that MRI is superior in pre-resectional glioma visualization ( 18 ) as well as in visualization of small tumor remnants ( 19 ). This finding is important ( Figure 1 ) despite the fact that in some cases glioma tissue may be better visualized by IOUS, as compared to high-field MRI ( Figure 2 ).…”
Section: Suboptimal Ultrasound Imagingmentioning
confidence: 99%